Thermal-Diffusion Effects on Mixed Convection Flow in a Heat Absorbing Fluid with Newtonian Heating and Chemical Reaction - Abid, Hussanan; Mohd Zuki, Salleh; Razman, Mat Tahar; Khan, Ilyas (2015)
Thermal-diffusion and chemical reaction effects on mixed convection heat and mass transfer flow past an infinite oscillating vertical plate with Newtonian heating is investigated. The governing equations are transformed to a system of linear partial differential equations using appropriate non-dimensional variables. Using Laplace transform method the resulting equations are solved analytically and the expression for velocity, temperature and concentration are obtained. They satisfy all imposed initial and boundary conditions. Numerical results for temperature and concentration are shown in various graphs for embedded flow parameters and discussed in details.